Dual-proxy key-based threshold signature scheme for ship ad-hoc network - Ming XU; Xuru LI; Chaobin LIU; Yao MA (Tongxin xuebao)
In order to solve the problem of message authentication under the conditions of the ship ad-hoc network (SANET),a signature scheme that does not depend on trusted certificate authorities and tamper-proof devices (TPD) was proposed by using the threshold proxy signature scheme and the properties of bilinear pairings.The proposed scheme used the dual-proxy key and the threshold signature mechanism to enable the ship nodes calculate the message signature in polynomial time.Moreover,the security of the scheme was also proved under the random oracle model.The performance analysis results show that the proposed scheme can meet the requirement of strong proxy signature under the premise of guaranteeing correctness,and has lower computational cost and communication cost.